Effectiveness of Implementing a Sleep Baby Kit (Baby Massage, White Noise, and Sleep Hygiene Education) in Improving Sleep Quality of Infants Aged 0–6 Months in the Working Area of Munjul Jaya Community Health Center - Mey Linda Darmayanti; Ayu Arifianingsih; Titin Prihantini; Karmilah; Neneng Maryamah (CV. Inara, 2026)
Sleep quality plays an important role in supporting the growth and development of infants aged 0–6 months. Sleep disturbances during this period can affect neurological maturation and growth hormone secretion, so an effective and safe non-pharmacological intervention is needed, namely the implementation of a Sleep Baby Kit. This study aimed to analyze the effectiveness of the Sleep Baby Kit, consisting of baby massage, white noise, and sleep hygiene education, on the sleep quality of infants aged 0–6 months in the working area of Munjul Jaya Community Health Center (Puskesmas), Purwakarta Regency. The study used a quasi-experimental pretest–posttest control group design with 66 respondents divided into an intervention group (n=33) and a control group (n=33). Sleep quality was measured using the BISQ-R before and after a four-week intervention. Data were analyzed using the Wilcoxon test and N-Gain analysis. The results showed that the proportion of infants with good sleep quality in the intervention group increased to 90.9%, while in the control group it was only 3.0%. The Wilcoxon test showed a significant improvement in the intervention group (p<0.001) and no significant improvement in the control group (p=0.109). The N-Gain value for the intervention group was 0.71±0.12 (high category), while the control group was 0.12±0.53 (low category). The Sleep Baby Kit is effective in improving the sleep quality of infants aged 0–6 months and has the potential to be applied as an evidence-based non-pharmacological intervention in primary health care.